Etiquette for Little Folks - Mackarness, Henry S., Mrs., 1826-1881 (Salt Lake City, UT : Project Gutenberg, 2022)
"Etiquette for Little Folks" by Mrs. Henry S. Mackarness is a guide on social behavior for children written in the mid-19th century. This instructive publication shares fundamental rules of propriety for young people, emphasizing the importance of manners, respect, and proper conduct in various social settings, such as at home, at the table, in school, and in public. The book is structured as a comprehensive manual for children, outlining specific behaviors expected in different environments. It offers practical tips, such as bowing to elders, sitting politely at the dining table, and interacting respectfully with peers and superiors. Each section details appropriate attitudes and responses, promoting virtues like humility, civility, and moral integrity. Through a series of concise rules, Mrs. Mackarness aims to shape children into well-mannered individuals who can navigate society gracefully, ultimately laying the groundwork for a more polished demeanor as they grow into adulthood. (This is an automatically generated summary.)
Release date is 2022-03-03
Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Etiquette for children and teenagers -- Juvenile literature